Menu Engineering: Evaluasi Produk Minuman (Kopi) di Kopiloka 3.0 Palembang - Lesmana, Andhika Chandra (Manajemen dan Pariwisata, 2024)
The coffee shop business in Indonesia is currently developing rapidly, especially in big cities such as Bandung, Jakarta, Surabaya, Medan, Bali, Palembang, and several other big cities, of course it is a big opportunity for entrepreneurs to open a business in this field, by various concepts or ideas that aim to attract customers from various circles, several cafes have even appeared in small towns in each region. South Sumatra is one of the 8 provinces producing the best coffee beans in Indonesia, with the dominant type of coffee being Robusta coffee. By seeing this opportunity, in the city of Palembang many coffee shops or what are usually called cafés are starting to appear, not only as a place to just drink a cup of coffee, but also as a place to relax, gather with friends, family, and even become a place to relax. to do a business, one of which is Kopiloka 3.0 Palembang. The function of a menu is to make it easier for visitors to choose what they want to order. A good menu can be seen from the level of sales and contribution in providing profits to the restaurant. Menu engineering is used to find out how much profit and actual food costs are, based on the basic cost and selling price of a product. In this menu evaluation, there are three indicators that will be discussed, namely popularity index, contribution margin, and menu classification. The method used in this research is a quantitative method with a descriptive approach, with data collection techniques in the form of observation, interviews, documentation studies and literature studies. The research results stated that the Popularity Index for the coffee menu was 88.64% for the HIGH category menu items and 11.34% for the LOW category menu items. The coffee menu items consist of 18 menus, for the HIGH category there are 14 menus and for the LOW category there are 4 menus; The contribution margin of the 18 coffee menu items served is that there are 9 menu items that fall into the HIGH category with a percentage of 58.17%. Meanwhile, 9 other menus fall into the LOW category with a percentage of 41.81%; Menu classification in the coffee menu, namely, there are 8 menu items included in the STAR category with a percentage of 55.24%, 6 menu items included in the PLOWHORSE category with a percentage of 33.4%, 3 menu items included in the DOG with a percentage of 8.41%, and 1 menu item which is included in the PUZZLE category with a percentage of 2.93%.